Penggunaan Metode Demonstrasi dalam Meningkatkan Hasil Belajar Siswa pada Pembelajaran IPA Kelas III-C Madrasah Ibtidaiyah Negeri 2 Malang - Nurul Ngainin (PUSAT PENELITIAN DAN PENGABDIAN KEPADA MASYARAKAT (P3M) SEKOLAH TINGGI ILMU TARBIYAH AL-FATTAH SIMAN LAMONGAN, 2021)
The purpose of this study was to determine the planning of the implementation of the use of demonstration methods and to improve student learning outcomes in science learning with earth form material in class III-C of Madrasah Ibtidaiyah Negeri 2 Malang. This research is a classroom action research conducted in two cycles. Each cycle consists of one meeting. The subjects of this study were students of class III-C Madrasah Ibtidaiyah Negeri 2 Malang. Data collection techniques using tests, observation and documentation. The results showed that in planning the use of the demonstration method, the researcher used 3 activity steps, namely the initial activity, the core activity and the final activity of the lesson. While the learning outcomes in the first cycle, completeness of learning outcomes reached a percentage of 65%. Whereas in the second cycle, it shows that the percentage of learning completeness reaches 99%, more than 75%. From the actions of the first cycle and the second cycle, it can be concluded that the use of the demonstration method can improve student learning outcomes in science learning earth form material in class III-C Madrasah Ibtidaiyah Negeri 2 Malang.